EXPLORING THE IMPACT OF DIGITAL TOOLS AND ONLINE RESOURCES ON LANGUAGE ACQUISITION AND ENGAGEMENT - Durdona Khamidova; Qurolova Shahlo (ResearchJet Journal of Analysis and Inventions, 2025)
Language learners now have a variety of options for interacting with new languages because to the quick development of digital tools and internet resources. With their increased accessibility, involvement, and engagement, digital platforms like virtual classrooms, online communities, and language-learning applications have completely changed the way that languages are taught and learned. With an emphasis on learner motivation, engagement, and competency development, this study examines how various digital technologies affect second language acquisition (SLA). This study examines the benefits and drawbacks of several digital tools for fostering language acquisition and long-term engagement using a mixed-methods approach that incorporates qualitative questionnaires and language performance analysis. The results show that although digital tools have many benefits, such as fast feedback and individualized learning routes, issues like student motivation and the possibility of passive consumption need to be addressed. The study comes to the conclusion that digital tools can greatly improve learner engagement and the acquisition process when properly incorporated into language training.